Jadid Dramaturgy and The Standardization of The Literary Language: The Paradigm of Reformism, The Concept of Lexical Renewal and Lexiconization - Rustamov Doniyorbek Avazbekovich (International Journal Of Literature And Languages, 2025)
The article examines the Jadid legacy at the center of drama and analyzes the impact of the reform movement (religious, cultural, educational, and political directions) on literary language. The connection of Jadid dramaturgy with the traditions of stage and folk theater, its role in raising social issues, and the enrichment of theater lexicon with units carrying the semantics of modernization are shown. To systematize the lexical layer in the work, a corpus-based dictionary program consisting of explanatory, etymological, thematic, ethnographic, paremiological, and author's dictionaries is proposed. As a result, Jadid plays are evaluated as a “living document” of the language of the period and are based on the reconstruction of the history of the language and the enrichment of modern norms as a reference source.